Legal Analysis, Default in Land Sale and Purchase (Case Study of Decision Number 119/Pdt.G/2024/PN Palangkaraya and Its Implications for Consumer Protection) - Frima Klin; Andika Wijaya; Ivans Januardy (Dinasti Research, 2025)
This study aims to analyze the application of civil law related to default in land sale and purchase through a case study of Decision No. 119/Pdt.G/2024/PN Palangkaraya. This study uses a normative legal method with a case study approach, where the primary data used are court decisions and secondary data in the form of laws and regulations and related legal literature. The main findings of this study indicate that the defendant has committed default by not fulfilling his obligations in changing the name of the Land Ownership Certificate, which resulted in losses for the plaintiff. The court decided to grant the plaintiff the right to take care of the name change independently, thus providing effective legal protection for consumers. The contribution of this study lies in an in-depth analysis of the implications of the decision on consumer protection in land sale and purchase transactions. This study enriches the discourse on consumer protection by highlighting the importance of strong law enforcement and simpler administrative procedures to prevent similar disputes in the future. In addition, this study provides a new perspective on the court's role in strengthening consumer legal protection in land disputes.